The Balanced Scorecard as a Strategic Management System in the Industry 5.0 Era: A Bibliometric Analysis (2000–2025) - Tuwanku Aria Auliandri; Dunga Dwi Barinta; Nurul Khaira; Elsa Yustika Putri; Andhy Setyawan; Teungku Ailishafia Auliandri (Universitas Hayam Wuruk Perbanas, 2026)
This study maps the intellectual structure, publication trends, and global collaboration patterns of Balanced Scorecard (BSC) research to examine its evolution from a performance measurement tool into a strategic management system (SMS) aligned with the Industry 5.0 paradigm. We conducted a descriptive quantitative bibliometric analysis of 736 documents indexed in Scopus between 2000 and 2025. Biblioshiny was used for performance and thematic analyses, whereas VOSviewer was used to map bibliometric networks. Publication output peaked in 2017 and showed renewed growth toward 2025. Thematic developments indicate a shift from a predominantly technocentric orientation toward the integration of Triple Bottom Line (TBL) and Environmental, Social, and Governance (ESG) considerations. The United States and the United Kingdom remain the leading contributors, although research activity has become increasingly decentralized, with rapid growth in China, Iran, and India. By providing a continuous 25-year synthesis, this study shows how the BSC has been reconfigured in response to sustainability imperatives and the human-centric orientation of Industry 5.0. The findings suggest that the BSC remains a relevant strategic instrument for aligning economic, social, and environmental objectives, particularly when embedded within ESG-integrated management architectures.